Pengaruh Persaingan Dan Kekuatan Pembeli Terhadap Hubungan Pemasok-Ritel Modern Di Jakarta - Dedie S. Martadisastra (Jurnal Manajemen, 2014)
The  aim  of the  study was to investigate the  development  of domestic supplier  perfrmances  as the  result of modem  retail-supplier  business  relationships which they  had  controlled  by the  effect of combinations  on competition and buyer power.  The  paper  presents  the  results  of a  survey  of packaged  processed  foods suppliers,  which  formed  part  of a  wider  study  of  buyer-supplier  relationships  in Indonesia's modem  retail supply chains. The findings of this study indicate that the results demonstrate the heterogeneity relationships between supplier and modem retail in the main commodity grocery sectors. The extent to which modem retail challenged by competition,  supply chain strategy and market share are likely to influence the way in  which modem retail deal with suppliers.  A part of the suppliers indicated that they get benefited  substantially from the presence of modem retail,  however, they also face several  challenges  brought    about  by buyer  power as  imposition  of several  unfair relationship terms, price fixing, and poorly supervision as cause of the development and growth of suppliers limitedly. This study attempts to show the results of the research in Indonesia to empirically measure the effect of competition and buyer power on modem retail-supplier relationships. The further research is needed to refine the results of this initial study.